2017
DOI: 10.1016/j.soilbio.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Functional differences in the microbial processing of recent assimilates under two contrasting perennial bioenergy plantations

Abstract: a b s t r a c tLand use change driven alteration of microbial communities can have implications on belowground C cycling and storage, although our understanding of the interactions between plant C inputs and soil microbes is limited. Using phospholipid fatty acids (PLFA's) we profiled the microbial communities under two contrasting UK perennial bioenergy crops, Short Rotation Coppice (SRC) willow and Miscanthus Giganteus (miscanthus), and used Functional differences in microbial communities were highlighted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 125 publications
(144 reference statements)
2
19
0
Order By: Relevance
“…Analytical Technologies Inc., USA) streamed to a G-2131i cavity ring down spectroscopy (CRDS) isotopic analyzer (Picarro Inc., USA) 46 . These values and the mass of necromass used in each assay were used to calculate δ 13 C of the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical Technologies Inc., USA) streamed to a G-2131i cavity ring down spectroscopy (CRDS) isotopic analyzer (Picarro Inc., USA) 46 . These values and the mass of necromass used in each assay were used to calculate δ 13 C of the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…20.00 and 09.00. Pulse labelling with 13 C in Miscanthus at this site has shown that C is available to soil microbes four hours after assimilation (Elias et al, ), and with highest rates of NEE seen from 11.00 to 15.00, photosynthate should start to arrive at the rhizosphere around 15.00. This coincided with the increase in N 2 O fluxes, and the arrival of plant C to the soil late in the day might also explain why R s remained above the daily average throughout the night time, despite coinciding with the lowest soil temperatures.…”
Section: Discussionmentioning
confidence: 94%
“…Within each plantation, four rectangular pulse chambers (6 m long x 2.5 m wide x 3 m high) were erected over the entire experimental plot (for full description of the experimental set-up see Elias et al, 2017). Briefly, a chamber volume of 45 m 3 allowed for the inclusion of two double rows of willow trees 1.5 m apart, whilst Miscanthus giganteus was randomly distributed in the 15 m 2 area.…”
Section: Co 2 Pulse Labelling Experimentsmentioning
confidence: 99%
“…Ostle et al, 2007;Seeber et al, 2012;Crotty et al, 2014;Huang et al, 2015). Nevertheless, very few have been performed in bioenergy crops (Tavi et al, 2013;Chaudhary and Dick, 2016;Elias et al, 2017) and our study is the first one trying to link soil macrofauna and rhizosphere carbon flow in these systems.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation